Implementation of proxmox server monitoring system with laravel and vue.js - Ariel Thymoti Irmawan; Raymond Maulany (Institute of Computer Science (IOCS), 2024)
Large organizations now heavily rely on Information Technology and Telecommunications (ICT) for their operations. Server availability is crucial in managing data centers and applications, but the increase in physical servers often involves high costs. Therefore, virtualization technology has emerged as an efficient solution. The research aims to develop the